Kebijakan Fiskal Dan Moneter Dalam Ekonomi Islam Perspektif Pemikiran Al Maqrizi - Fadilah, Dimas; Rosyid, Abdul; Wartoyo, Wartoyo (Jurnal Inovasi Global, 2025)
This study aims to examine Al-Maqrizi's economic thought regarding fiscal and monetary policy in depth and evaluate its relevance in the context of contemporary Islamic economics. Using a qualitative approach and literature review of Al-Maqrizi's main work Ighātsah al-Ummah bi Kashf al-Ghummah, this study identifies Al-Maqrizi's critical thinking on the phenomena of inflation, fiscal injustice, and monetary instability that occurred during the Mamluk Dynasty. Al-Maqrizi distinguishes inflation into two types: natural inflation caused by external factors and artificial inflation caused by human error, such as corruption, excessive taxation, and uncontrolled money printing. In the fiscal aspect, he emphasizes the importance of justice in the tax system, the optimization of zakat for wealth distribution, and efficiency in managing state expenditures. In monetary policy, he advocated the use of the dinar-dirham currency standard and rejected the practice of mixing metals that degraded the quality of money. His ideas align with modern economic theories, such as Gresham's Law and the quantity theory of money, while reaffirming Sharia principles that prioritize justice and balance. Research findings indicate that Al-Maqrizi's contributions are relevant in designing a fair, ethical, and sustainable Islamic economic policy system and can serve as an important reference for Muslim countries in addressing contemporary economic challenges.